Bureaucratic minimal squawk behavior: theory and evidence from regulatory agencies - Leaver, C (University of Oxford, 2007)
This paper argues that bureaucrats are susceptible to 'minimal squawk' behavior. I develop a simple model in which a desire to avoid criticism can prompt, otherwise public-spirited, bureaucrats to behave inefficiently. Decisions are taken to keep interest groups quiet and mistakes out of the public eye. The policy implications of this behavior are at odds with the received view that agencies should be structured to minimise the threat of 'capture'. I test between theories of bureaucratic behaviour using a matched panel of U.S. State Public Utility Commissions and investor-owned electric utilities. The data soundly reject the capture hypothesis and are consistent with the minimal squawk hypothesis: longer PUC terms of office are associated with an increase in the incidence of rate reviews in period of falling input costs and, in turn, lower household electricity bills.